Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.143
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Document-Level Polarity Classifiers Fail?

Abstract: Machine learning solutions are often criticized for the lack of explanation of their successes and failures. Understanding which instances are misclassified and why is essential to improve the learning process. This work helps to fill this gap by proposing a methodology to characterize, quantify and measure the impact of hard instances in the task of polarity classification of movie reviews. We characterize such instances into two categories: neutrality, where the text does not convey a clear polarity, and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Also note that the human performed worse (Accuracy: 45.83%) on instances where the machine classifier error was higher (Table 12), when compared to the performance (Accuracy: 50%) on instances where the machine classifier error was lower (Table 13), indicating that, in fact, this group of instances may have more misleading texts. Considering the two types of hardest instances proposed by Martins et al [24], for 21 (22%) instances the annotator was not certain about their polarities, that is, 22% of the instances in this sample are neutral hard instances. The accuracy for these instances was only 23% (Table 14), significantly lower than for the instances in which the annotator did not have any doubt: 54.66% (Table 15).…”
Section: Review Score Prediction (Rsp)mentioning
confidence: 81%
See 3 more Smart Citations
“…Also note that the human performed worse (Accuracy: 45.83%) on instances where the machine classifier error was higher (Table 12), when compared to the performance (Accuracy: 50%) on instances where the machine classifier error was lower (Table 13), indicating that, in fact, this group of instances may have more misleading texts. Considering the two types of hardest instances proposed by Martins et al [24], for 21 (22%) instances the annotator was not certain about their polarities, that is, 22% of the instances in this sample are neutral hard instances. The accuracy for these instances was only 23% (Table 14), significantly lower than for the instances in which the annotator did not have any doubt: 54.66% (Table 15).…”
Section: Review Score Prediction (Rsp)mentioning
confidence: 81%
“…In the other direction, Krymolowski [19] defines hard instances as those that lead to a higher probability of error. Martins et al [24] proposed a methodology for finding hard instances in movie reviews and showed that such instances are significantly more difficult to classify. To the best of our knowledge, only Wang and Wan [32] evaluated the impact of hard instances on the paper review classification task.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations